Necroptosis and Viral Myocarditis: Tumor Necrosis Factor α as a Novel Biomarker for the Diagnosis of Viral Myocarditis - Zhou, Jin; Xu, Jing; Li, Peng; Sun, Shan; Kadier, Yimiti; Zhou, Shiying; Cheng, Aijuan (Frontiers in Cell and Developmental Biology, 2022)
Programmed cell death (PCD), including necroptosis, has emerged as a significant pathway in cardiovascular diseases. The infection of viral myocarditis (VMC) could cause cardiomyocytes degeneration, necrosis, and immune-inflammatory myocardial response. In this review, we summarized and evaluated the available evidence on the pathogenesis, molecule mechanism, diagnosis, and potential treatment strategies of viral myocarditis, with a special focus on the novel mechanism of necroptosis for cardiomyocytes death. Studies have shown that tumor necrosis factor-alpha (TNF-α) is an important cytokine involved in the activation of necroptosis; an elevated level of TNF-α is continually reported in patients suffering from VMC, implicating its involvement in the pathogenesis of VMC. It is of great interest to explore the clinical implication of TNF-α. We subsequently conducted a meta-analysis on the efficacy of serum TNF-α expression level and its diagnostic accuracy on acute viral myocarditis detection. Taken together, the review demonstrates a compelling role of necroptosis involved in the pathogenesis of VMC. Further, applying TNF-α as a serological marker for the diagnosis of VMC may be a useful strategy.